Cold Acclimation and Deacclimation of Winter Oilseed Rape, with Special Attention Being Paid to the Role of Brassinosteroids - Stachurska, Julia; Sadura, Iwona; Jurczyk, Barbara; Rudolphi-Szydło, Elżbieta; Dyba, Barbara; Pociecha, Ewa; Ostrowska, Agnieszka; Rys, Magdalena; Kvasnica, Miroslav; Oklestkova, Jana; Janeczko, Anna (International journal of molecular sciences, 2024)
Winter plants acclimate to frost mainly during the autumn months, through the process of cold acclimation. Global climate change is causing changes in weather patterns such as the occurrence of warmer periods during late autumn or in winter. An increase in temperature after cold acclimation can decrease frost tolerance, which is particularly dangerous for winter crops. The aim of this study was to investigate the role of brassinosteroids (BRs) and BR analogues as protective agents against the negative results of deacclimation. Plants were cold-acclimated (3 weeks, 4 °C) and deacclimated (1 week, 16/9 °C d/n). Deacclimation generally reversed the cold-induced changes in the level of the putative brassinosteroid receptor protein (BRI1), the expression of BR-induced COR, and the expression of SERK1, which is involved in BR signal transduction. The deacclimation-induced decrease in frost tolerance in oilseed rape could to some extent be limited by applying steroid regulators. The deacclimation in plants could be detected using non-invasive measurements such as leaf reflectance, chlorophyll a fluorescence, and gas exchange monitoring.
Keywords: Acclimatization; Seasons; frost tolerance; listy rostlin; 28-homocastasterone; Brassinosteroids; Plant Proteins; chlorophyll a fluorescence; brassinosteroid analogues; BRI1; Plant Leaves; aklimatizace; roční období; Cold Temperature; rostlinné proteiny; COR; Brassica napus; 24-epibrassinolide; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; SERK; CO2 assimilation; leaf reflectance; nízká teplota; brassinosteroidy